Security Improvisation through Node Trust Prediction Approach in Mobile Ad Hoc Networks - Raghavendar Raju, L; Reddy, C R K (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Identifying trusted nodes for safe communication is a key challenge in mobile ad-hoc networks. Node compromises a service and leads to uncertainty in node behaviour. Computing the node trust and node management will enhance the security aspect in MANETs. This paper proposes a security improvisation based on a Node Trust Prediction Approach (NTPA). NTPA aims to prevent the interference of an anomalous node in a MANET. There by improving the security and data delivery output. The NTPA calculates the node trust prediction by evaluating the four most frequent actions that are performed by a node in the communication process. Node authorization is a key aspect in the evaluation of an ad hoc network’s security. In the proposed method, we monitor the valid and Invalid Authorization of a node. Data delivery reliability is measured with Success of Packet delivery and Loss or Drop of packets. In this paper, NTPA is compared with SAR(Security-Aware Routing) and AODV (Adhoc on-Demand Distance Vector), to evaluate the efficiency in an adhoc networks. The empirical results shows that there is an increase of 25% packet delivery and a 40% reduction in routing overhead.